Concentration and BNDES loans in Brazil: can a development bank bolster market power? - Magalhães, Paula Karine Ribas (2024)
This study examines the dynamics of market concentration and the role of industrial policy in shaping market power within Brazil, a key emerging market. Utilizing firm-level data from publicly traded companies and formal sector employment records, we investigate trends in market concentration and its implications for economic policy. Despite the theoretical foundations of perfect competition, our findings reveal an increasing market concentration among publicly traded firms in Brazil, unattributed to stock market dynamics and persistent even when excluding a monopolistic sector such as Oil. Furthermore, we extend our analysis to the broader Brazilian market through the RAIS database, uncovering a similar, albeit slower, increase in concentration across all firm sizes. This paper also explores the relationship between subsidized lending by the Brazilian Development Bank (BNDES) and market concentration, finding a notable correlation post-2002, suggestive of the Bank’s loans potentially facilitating increased market power among recipient sectors. Employing a shift-share design, we analyze the impact of BNDES loans on concentration in sectors and wage levels, discovering that loans have bolstered market share and wages. These findings contribute to our understanding of market dynamics in emerging economies and the nuanced effects of industrial policy, challenging the assumption of decreasing labor shares in the economy and providing a comprehensive view of concentration trends and their determinants in Brazil.